Answer:
3x+y=-1
Explanation:
Standard form is ax+by=c.
So we need to get the x-term and the y-term on the same side together.
First step: Distribute:
y-5=-3x-6
Second step: Add 5 on both sides:
y=-3x-6+5
Third step: Simplify:
y=-3x-1
Fourth step: Add 3x on both sides:
3x+y=-1
We are done because this is in ax+by=c form where a=3,b=1, and c=-1.
The form we started with in this problem is point-slope form:
.
So if you follow those steps above for point-slope form you should get your standard form.
Let's do this for the general case.
First step: Distribute:
![y-y_1=mx-mx_1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/y6m0la4s5gs8q281qfb8ef2j7g6gwrz6ju.png)
Second step: Add
on both sides:
![y=mx-mx_1+y_1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/r9561muakzkxix7sfl8i8ta754k1sasu9f.png)
Third step: Simplify:
![y=mx+(-mx_1+y_1)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/erj772fa4bxdcry3voc8rg15fzq88fbj7c.png)
Fourth step: Add -mx on both sides:
![y+-mx=-mx_1+y_1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/j6zeq222heqbw0tajovlvb3owwkm4qms5l.png)